Web crippling behaviour of LiteSteel Beams with edge-stiffened web openings under End-Two-Flange load case - Elilarasi, K.; Janarthanan, B.; Athapaththu, D.; Poologanathan, K.; Perampalam, G. (University of Jaffna, 2022)
Cold-Formed Steel (CFS) members are widely used with openings in the floor system for various service purposes such as power, telecommunication, and internet cables. Also, web crippling is becoming vulnerable owing to the impact of web openings. However, stiffened web openings are expected to increase the web crippling capacity and redeem a significant percentage of the actual capacity of the section without web openings while allowing the service integration. This paper presents the numerical study on the web crippling capacity of LiteSteel Beams (LSB) with centred beneath stiffened web openings under the End-Two-Flange (ETF) load case. Although Rectangular Hollow Flange beams are investigated with centred beneath web openings, no studies have been carried out regarding stiffened web openings. Therefore, results from previous studies on the web crippling of channel sections with stiffened web openings were validated in terms of strength and failure mode; a good agreement was observed in the validation. Subsequently, parametric study was conducted using Abaqus; Finite Element Analysis (FEA) software, by considering various section depths, bearing plates, yield strengths, web opening ratios, thicknesses, and stiffener lengths of the hole. The FEA results showed much improvement in the web crippling capacity with edge-stiffened openings and the FEA results were analysed with various parameters for better predictions in terms of web crippling strengths.
Keywords: Cold-Formed Steel; LiteSteel Beam; Web crippling; End-Two-Flange; Finite Element Analysis; Edge-stiffened openings